Validation of DIGIROP models and decision support tool for prediction of treatment for retinopathy of prematurity on a contemporary Swedish cohort - Pivodic, Aldina (2022)
The Gothenburg Medical Society and Government grants under the ALF agreement (ALFGBG-717971), De Blindas Vänner (no grant number) and Knut and Alice Wallenberg Clinical Scholars (no grant number). LEHS was supported by National Eye Institute (EY017017 and EY030904) and National Institute of Health (1U54HD090255).